MODEL EDUCATION RECONSTRUCTION (MER) BAHAN AJAR PENELITIAN LABORATORIUM (PL) KONTEKS ZEOLIT BERBASIS PROBLEM SOLVING-DECISION MAKING (PSDM) - Doloksaribu, Florida; Mudzakir, Ahmad; Sholihin, Hayat; Sudargo, Fransiska (Jurnal Penelitian Pendidikan, 2014)
Abstract. Aspects discussed in this research is to improve the intelligence thinking of student research through a MER (Duit 2012). Based on a problem that is often found that the appearance of lack of originality of research because students are not able to think of research, which is shown in a preliminary study.Based on these problems, researchers developed teaching materials to reconstruct RL context zeolite based PSDM. The instrument was a questionnaire response experts to determine the feasibility of the cognitive level of the student materials in accordance with the character of the curriculum in 2013. The characteristics of instructional materials: 1) was developed in accordanceaspect PSDM attitude Myers-Briggs Type Indicator (MBTI), 2) the context ofthe lecture corresponding zeolite mineral chemistry issues, 3) content according to the level of cognitive student accesible criteria, 4) Perspective students to the concept of material through interviews. Interviews showed> 80% of the students have any preconceptions about the meaning of the scientific method and thinking research. Therefore, the insertion of material thought PSDM based research on teaching materials need to be raised. Validation / CVR obtain the Value 0.76, and CVI c(0,76) > CVI t(0,68) showed very appropriate instructional materials used.